Serum Interleukin-4 and Total Immunoglobulin E in Nonatopic Alopecia Areata Patients and HLA-DRB1 Typing - Enas A. S. Attia; Dina El Shennawy; Ashraf Sefin (Hindawi Limited, 2010)
Background. Interleukin-4 (IL-4), a Th2 cytokine, can stimulate immunoglobulin E (IgE) transcription. No previous studies evaluated the genetic mechanisms in nonatopic AA patients with elevated serum IgE. Objective. To compare serum IL-4 and total IgE levels between Egyptian nonatopic AA patients and healthy subjects and to investigate a possible relation to HLA-DRB1 alleles. Results. Serum IL-4 and total IgE were measured by ELISA in 40 controls and 54 nonatopic AA patients. Patients' HLA-DRB1 typing by sequence specific oligonucleotide probe technique was compared to normal Egyptian population. We found significantly elevated serum IL-4 and total IgE in AA patients (particularly alopecia universalis, AU, and chronic patients) (P<.01). HLA-DRB1*11 is a general susceptibility/chronicity allele. DRB1*13 is a protective allele. DRB1*01 and DRB1*07 are linked to chronicity. Localized AA showed decreased DRB1*03 and DRB1*07. Extensive forms showed increased DRB1*08 and decreased DRB1*04. Elevated IL4 and IgE were observed in patients with DRB1*07 and DRB1*11 not DRB1*04. Conclusion. Serum IL-4 and IgE are elevated in nonatopic AA patients, particularly AU and chronic disease. Relevant susceptibility, chronicity, and severity HLADRB1 alleles may have a role in determining type, magnitude, and duration of immune response in AA favouring increased IL4 and IgE.